LEGAL PROTECTION FOR VICTIMS OF THE CRIMINAL ACT OF BUYING AND SELLING PORNOGRAPHIC CONTENT VIA TELEGRAM SOCIAL MEDIA - Alan Dedy Hernando D (JILPR Journal Indonesia Law and Policy Review, 2026)
Legal protection for victims of the crime of buying and selling pornographic content through the Telegram application is a concrete manifestation of the state's responsibility in guaranteeing the human rights of every citizen to obtain a sense of security, protection, and justice in the digital space. The problem in this study is how legal protection for victims of the crime of buying and selling pornographic content through Telegram social media and what obstacles are found in realizing legal protection for victims of the crime of buying and selling pornographic content through Telegram social media. In addition to limited personnel and technical capabilities, the factor of facilities and infrastructure is also a major obstacle in handling pornography crimes through Telegram. Many regional police cyber units are not equipped with adequate supporting devices, such as cyber monitoring systems, digital forensic devices, and the latest online activity tracking software. This study uses a normative legal research method by reviewing document studies using various secondary data such as laws and regulations, court decisions, legal theories, and can be in the form of scholarly opinions. This study concludes that ideal legal protection for victims of pornography crimes in the digital space does not only emphasize the punishment of the perpetrator, but must also include comprehensive protection for victims through legal assistance, guarantees of identity confidentiality, and psychological and social recovery. These efforts need to be accompanied by increased capacity of law enforcement officials in information technology, modernization of cyber law enforcement facilities, and strengthening cross-border cooperation with digital platform providers like Telegram. Going forward, more specific regulatory updates regarding digital pornography are needed, particularly regarding the mechanisms for trading content on closed platforms like Telegram, including rules regarding paid memberships, private groups, and digital asset-based transactions.